The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bbcan.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum-mediated unfolded protein response and mitochondrial apoptosis in cancer

Abstract: Abrogation of endoplasmic reticulum (ER) protein folding triggered by exogenous or endogenous factors, stimulates a cellular stress response, termed ER stress. ER stress reestablishes ER homeostasis through integrated signaling termed the ER-unfolded protein response (UPRER). In the presence of severe toxic or prolonged ER stress, the pro-survival function of UPRER is transformed into a lethal signal transmitted to and executed through mitochondria. Mitochondria are key for both apoptotic and autophagic cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 136 publications
1
85
0
Order By: Relevance
“…The ER stress response exists in diverse biological systems and plays roles in the regulation of cell proliferation in many tumor cells . There is also evidence that the induction of ER stress proteins plays a role in apoptosis in various cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…The ER stress response exists in diverse biological systems and plays roles in the regulation of cell proliferation in many tumor cells . There is also evidence that the induction of ER stress proteins plays a role in apoptosis in various cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Although diverse mechanisms for melatonin-induced apoptosis have been suggested, many of them have the same denominator — ER stress. Activation of the mitochondrial pathway of apoptosis is deeply dependent on calcium release from the ER due to ER stress [55, 59]. We have shown that in tumour cells, melatonin is able to induce ER stress and activate the apoptotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a highly regulated process to induce apoptotic cell death. Increased expression of ER stress markers (GRP78, CHOP and caspase12) have been reported to activate apoptosis, as they are critical mediators during ER stress-mediated apoptosis [32, 33]. Thus we also studied the changes of ER stress and apoptosis.…”
Section: Discussionmentioning
confidence: 99%